The technology of the installation of church bells - Chebanov, L.; Kozlenko, D.; Shulhach В. (Ways to Improve Construction Efficiency, 2019)
In the construction of new and reconstruction and reconstruction of historical churches and bell towers in different regions of Ukraine, there are issues of designing and designing of suspended systems of large bells, the characteristics of which would minimize the dynamic and vibrational loads that arise during the ringing, create the best conditions for implementing the sound characteristics of bells , while providing security and convenience for callers. The bells have a considerable mass, they are installed at altitude, often under confined conditions.